Baby Altruists? Examining the Complexity of Prosocial Motivation in Young Children. (24th August 2012) - Thompson, Ross A.; Newton, Emily K.
<x xml:space="preserve">Abstract</x> The contributions of these studies to our understanding of early prosocial motivation are discussed in the context of the broader research literature in this field. We consider first whether different forms of prosocial behavior (e.g., helping, sharing, and empathic assistance) reflect a core prosocial disposition in the early years. The methodological challenges of assessing prosocial behavior in very young children are considered next. We then discuss the origins of prosocial motivation in the early years, focusing on developing understanding of others' goals and intentions, the emergence of sensitivity to equity, emotion understanding, and other conceptual advances. We conclude with suggestions for future research directions for this exciting field of study.